The moral and legal issues of the (non)patentability of the human embryonic stem cell related inventions. : Comparative study: European and U.S perspective - Puisto, Iina (My University, 2021)
Within the times of significant growth in the amounts of biotechnological inventions, certain legislative issues have risen high on their importance. While affecting to the life of many, some of the biotechnological inventions raise controversial thoughts in public at large, as well as amongst the legislators and decision-making bodies. The use of human embryonic stem cell related inventions have been a center of debate ever since the first breakthroughs – especially regarding its patent eligibility and use for commercial purposes contradicting with the question of infringing human dignity. Having struggled on providing consistent interpretations of the related laws in Europe have caused doubts on the effectiveness of the regulations, as well as a fear of impeding innovation and research by excluding certain areas wholly out of the scope of patentability and rather relocating it elsewhere. Thus, this thesis compares the different treatment of human embryonic stem cell related inventions and their patentability in the Europe and U.S. This study critically analyzes the current situation of the regulation concerning biotechnological inventions in Europe and compares it to the patent realm in the U.S, as well as focuses on finding out whether the contradicting interest of the public could be resolved in ways of securing both by encouraging innovation through an incentive to patent with safeguarding human dignity and avoiding the misuse of the human embryos at the same time. How, in fact, have the Europe´s exclusive approach affected the prominent stem cell research as their patentability is prohibited on the grounds of immoral actions and ordre public in Europe? Is there really a need for a morality clause in patent law or could the same measures be presented otherwise, and if so, how? This thesis is a theoretical research operated in a comparative manner and the sources used here are a combination of different academic reviews, books and articles. The use of relevant applicable laws and regulations are provided with an emphasis to the existing case law concerning the human embryonic stem cells both in Europe and U.S.

Bioteknologisten keksintöjen määrän kasvaessa tietyt lainsäädännölliset seikat ovat näyttäytyneet ongelmallisina sekä vaikeasti tulkittavina, jotka ovat osaltaan johtaneet epäjohdonmukaisiin päätöksiin alkiokantasolukeksintöjen keskuudessa sekä niitä patentoitaessa. Kyseessä ollessa ajoittain elintärkeät keksinnöt sekä mahdollisuus löytää parannuskeinoja jopa kuolemaan johtaviin sairauksiin, niiden tärkeys on noussut merkittävään asemaan. Tutkimuksen sekä keksintöjen kuitenkin koskiessa ihmisalkioiden kantasoluja, etenkin niiden patentoitavuus ja käyttö kaupallisiin tarkoituksiin on herättänyt paljon kiistanalaisia ajatuksia niin yhteiskunnassa yleisesti kuin lainsäätäjien ja päättäjienkin keskuudessa, sillä ristiriita ihmisarvon loukkaamisesta on ilmeinen. Eri tahojen epäonnistuessa tarjota johdonmukaisia tulkintoja asiaankuuluvien lakien osalta Euroopassa on aiheuttanut epäilyä regulaatioiden tehokkuudesta sekä pelkoa siitä, että sulkemalla tietyt keksinnönlajit täysin patentoitavuuden ulkopuolelle, lait toimivat ennemmin esteenä tai hidasteena tutkimukselle sekä innovaatiolle siirtäen kehityksen muualle. Näin ollen, tämä tutkimus vertaa alkiokantasolukeksintöjä ja niiden patentoitavuuden erilaista kohtelua Euroopan sekä Yhdysvaltojen välillä, sekä kriittisesti analysoi bioteknologisia keksintöjä koskevaa lainasäädännön nykytilannetta Euroopassa, selvittäen samalla, onko ilmeneviä ristiriitoja eri perusoikeuksien osalta mahdollista ratkaista siten, että innovaation kannustin säilyy ihmisoikeuksia loukkaamatta välttäen ihmisalkioiden väärinkäyttö, kuten esimerkkinä niiden massatuotanto. Tiivistäen tutkimuksen kokonaisuutta, eurooppalaisen poissulkevan lähestymismallin vaikutuksia kantasolututkimukselle on tarkasteltu siitä näkökulmasta, onko moraalilausekkeelle todella tarvetta patenttilaissa, vai voitaisiinko niistä todellisuudessa säätää muilla tavoin kuin jättämällä ne täysin patentoitavuuden ulkopuolelle moraalittomiin toimiin ja ordre public -periaatteeseen vedoten. Tämä pro gradu -tutkielma on toteutettu vertailevaa menetelmää käyttämällä, ja sen pääasialliset lähteet ovat yhdistelmä erilaisia oikeustieteellisissä tietolähteissä julkaistuja artikkeleita sekä muita akateemisia kirjoituksia ja teoksia. Asiaankuuluvien lakien ja asetusten käyttö on olennainen osa tätä tutkielmaa ja ihmisalkion kantasoluja koskevaa nykyistä oikeuskäytäntöä Euroopassa ja Yhdysvalloissa on myös painotettu.
Keywords: immaterial property rights, patent law, biotechnology, human embryonic stem cells, comparative law, international law immateriaalioikeudet, patenttilait, bioteknologiset keksinnöt, alkiokantasolupatentti, EU oikeus, kansainvälinen oikeus